Partial characterization of the polluting load of swine wastewater treated with an integrated biodigestion system - Ferreira, FLA; de Lucas, J.; do Amaral, L. A. (Elsevier B.V., 2003)
The stabilization of swine wastewaters from swine confined housing by the combination of a upflow anaerobic sludge blanket (UASB) reactor and waste stabilization ponds is a viable alternative to minimize the environmental impact caused by inadequate disposal of swine wastewaters. In the present study, the polluting load of pre-decanted swine wastewater treated with a series of two 0.705 m(3) UASB reactors and then in parallel in aerated and non-aerated stabilization tanks was investigated from January to July, 2000. Physicochemical and microbiological analyses were made adopting standard methods (Standard Methods for Examination of Water and Wastewater, 19th ed., American Public Health Association, Washington, DC, 1995). COD values decreased as the wastewater ran through the integrated biodigestion system dropping from about 3492 +/- 511-4094 mg l(-1) +/- 481 to 124 +/- 52-490 mg l(-1) +/- 230, while nitrate and nitrite levels increased in stabilization tanks, ranging respectively from 4 +/- 0 to 20 mg l(-1) +/- 3 and 3 +/- 1 to 11 mg l(-1) +/- 24. Although the removal of Escherichia coli was more than 97% +/- 6, the effluents of the treatment system still contained unacceptable levels of E. coli (1.6 x 10(3)-1.2 x 10(6) 100 ml(-1)) according to WHO guidelines for use of wastewater in agriculture and aquaculture. These results indicate the necessity of changes on operational characteristics of the treatment system such as an increase of the hydraulic retention time in UASB reactors or in stabilization tanks. (C) 2003 Published by Elsevier Ltd.
Keywords: Swine wastewater; UASB reactor; stabilization tanks; Escherichia coli; nitrate